(untitled) (Anwer Khan Modern Medical College Journal, 2020)
Background: Rape is a very alarming situation in the context of Bangladesh. It is the most common form of violence against woman. In Bangladesh, rape is found as the second commonly reported form of violence against women, following dowry related harassment. However, sexual violence has a great impact on physical and mental state of health with an increased range of sexual & reproductive health problem. Objectives: To describe rape victims medico-legal examination findings those includes sociodemographic characteristics, location of victim’s residence, victims signs of struggle / violence & condition of hymen, status of victims vaginal swab test report, state of victim’s mental condition & sexual abuse, state of victim’s sign of Non-Genital Violence & state of accused and victim’s status of pregnancy as well. Methods: This was a descriptive type of cross-sectional study taken from a retrospective record review which was done in the Department of Forensic Medicine, Shaheed Suhrawardi Medical College, Dhaka, Bangladesh from 29th Oct 2017 to 30th Sep 2019 with the support of department faculties in reviewing the records using a checklist. Results: More than 60% victims were within 15-29 years of age with mean age 18.69 years and SD: + 5.921. Among the victims 27.5% had no formal education & almost 78% victims’ occupation was student and garment workers. The study revealed that 76.3% victims were single (Unmarried) and 34.8% & 19.3% of the victims’ residence was Ashulia, & Dhamrai respectively. Among the victims only 67.6% had the consent for medico-legal examination. Signs of struggle / violence was present only on 5.71% and ruptured hymen was found in 96.43% of victims respectively. Negative spermatozoa were found among all respondents. All of the respondents were found as Anxious and depressive. Moreover, state of sexual abuse was present among 98.57% respondents and 96.43% victims had the state of non-genital violence. Almost 95% of the victim’s examination was done between more than 7 days to 1 month. Only 5% of the victims were found pregnant. Conclusion: The study findings demand a growing need focusing in developing strategies for the care & support of rape victims. An adequate legal coverage for the rape victims, a post rape health and social services can be considered an unmet need for the society in deed. Anwer Khan Modern Medical College Journal Vol. 11, No. 1: Jan 2020, P 41-45